Pemberdayaan UMKM Desa Curug Sulanjana di Era Digital melalui Sosialisasi KKN: Membangun Semangat dan Kreativitas Berwirausaha: Pengabdian - Deti Kurniati; Ovi Fitriyah; Adhelia Permata Shafrina Afiro; Novi Fitriyah; Wafiro; Bilqis Novriana Pratama (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
A socialization activity for MSMEs with the theme “Building Entrepreneurial Spirit and Creativity in the Digital Age” was held by KKN students as a form of community service. The event was attended by 24 participants from the UMKM community of Curug Sulanjana Village. The objective was to provide an understanding of digital technology utilization, foster entrepreneurial spirit and creativity, and assist participants in building their business identity through logo creation. The methods employed included presentations, interactive discussions, and direct mentoring. The results of the activity showed that participants gained new insights into digital marketing strategies, were more motivated to innovate, and successfully created simple business logos as visual identities. This activity not only benefited the SMEs but also provided valuable experience for the KKN students in community empowerment.